2015
DOI: 10.2527/jas.2015-9547
|View full text |Cite
|
Sign up to set email alerts
|

Diets of differentially processed wheat alter ruminal fermentation parameters and microbial populations in beef cattle1

Abstract: The influences of differently processed wheat products on rumen fermentation, microbial populations, and serum biochemistry profiles in beef cattle were studied. Four ruminally cannulated Limousin × Luxi beef cattle (400 ± 10 kg) were used in the experiment with a 4 × 4 Latin square design. The experimental diets contained (on a DM basis) 60% corn silage as a forage source and 40% concentrate with 4 differently processed wheat products (extruded, pulverized, crushed, and rolled wheat). Concentrations of rumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Starch digestibility was almost complete for all wheat treatments, indicating excellent utilization of the wheat grain, as reported by Sinclair et al (2003) for wheat of relatively similar chemical composition when using a fecal collection method. We have studied the effects of different methods of processing wheat on nutrient digestibility, digestive enzyme activities and serum metabolite concentrations of beef cattle (Jiang et al, 2015) and found that the digestibility of DM, OM, CP, NDF, and ADF in a puffed wheat diet was significantly higher than that in the other three diets (p<0.05). The digestibility of DM and OM in both the ground wheat diet and the crushed wheat diet was significantly higher than that in squashed wheat diet (p<0.05), and the digestibility of NDF and ADF in the ground wheat diet was significantly lower than that in the other diets (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Starch digestibility was almost complete for all wheat treatments, indicating excellent utilization of the wheat grain, as reported by Sinclair et al (2003) for wheat of relatively similar chemical composition when using a fecal collection method. We have studied the effects of different methods of processing wheat on nutrient digestibility, digestive enzyme activities and serum metabolite concentrations of beef cattle (Jiang et al, 2015) and found that the digestibility of DM, OM, CP, NDF, and ADF in a puffed wheat diet was significantly higher than that in the other three diets (p<0.05). The digestibility of DM and OM in both the ground wheat diet and the crushed wheat diet was significantly higher than that in squashed wheat diet (p<0.05), and the digestibility of NDF and ADF in the ground wheat diet was significantly lower than that in the other diets (p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if and how the changes reported by Van Gastelen et al [10] in CH 4 emissions and fermentation characteristics are related to changes in the rumen microbiota. Additionally, the majority of rumen microbial studies to date have primarily focused on starch in the context of cereal grains [2,11,12] rather than different types of roughages. Hence, the objectives of the present study were (1) to investigate the effect of replacing fiber-rich GS with starch-rich MS on the rumen bacterial and archaeal diversity and concentrations using samples collected 10 and 17 days after the introduction of the experimental diets, and (2) to place the findings in the context of ruminal fermentation as well as previously reported data on CH 4 emission [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in some places where these technologies are emerging, methods for the storage of ruminal samples for microbiological analyses, occasionally for several months depending on experimental conditions and financial resources, are required. To date, there are no standard rumen sample storage methods used before DNA extraction; however, the most commonly used among these methods are lyophilisation [6, 13, 14], freezing at -80°C [2, 7, 1518] or at -20°C [1922], and the storage of rumen microbial samples as pellets with the use of buffer solutions [2328]. However, previously mentioned studies did not refer to the ruminal sample storage time before the extraction of metagenomic DNA.…”
Section: Introductionmentioning
confidence: 99%